Kemasan Produk Kreatif di Era Digital: Pelatihan Canva Bagi Pelajar SMA - Jusbaeni Jusbaeni; Umara Hasmarani Rizqiyah; Nahridzah Mahjubuh Shiber; Husnirrahman J; Syahrul Syahrul (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
The development of digital technologyhas had a significant impact on education and the creative economy. The ability to processvisual designs has become an important skill for the younger generation to face thechallenges of the digital age. This community service activity aims toimprove students' digital design skills and creativity throughCanva training as a practical learning medium. The trainingwas conducted at SMAN 22 Gowa, involving six students from grades X and XI.The implementation method used an interactive workshop approach and hands-on practice(learning by doing) that emphasised project-based learning experiences. The results of the activity showed an increase in students' ability to understandthe basic principles of packaging design, apply visual elements appropriately, andproduce creative and communicative design works. This activity also fostered self-confidence,collaborative spirit, and awareness of the importance of digital literacy. Thus, this training successfully contributed positively to thedevelopment of creative skills and the readiness of students to face the world ofentrepreneurship and technology-based creative industries (Bell, 2010; Guo et al.,2020; Supriyadi, 2023; Wicaksono & Indriani, 2022).